Auditor Experience as a Moderation of the Effect of Audit Fees, Audit Tenure, and Task Complexity on Audit Quality - Setiyo Hadi Santoso; Umi Muawanah; Oyong Lisa (International Journal Labs, 2023)
Audit quality is the ability to obtain good quality or not the examination that has been carried out through the auditor. The study was conducted because there are cases of audit failure related to audit quality which are suspected to be due to audit fees, audit tenure, task complexity and auditor experience due to inconsistency of the influence of previous analysis. The research was conducted to find out the empirical evidence of the auditor's experience as moderating variables of audit fees, audit tenure and task complexity regarding audit quality. The method of analysis is a quantitative approach, applying a survey process through a questionnaire (question list). The population in the analysis, namely auditors as respondents at 70 East Java Regional Public Accounting Firms, has been recorded in the IAPI 2021 Directory. In evaluating the suitability of the method in the analysis, validity, reliability and descriptive statistics are carried out. Statistical research technique using multiple linear analysis using SPPS 26. Auditor experience is able to strengthen the interaction between audit fee factors, audit tenure, and task complexity on audit quality.